2019
DOI: 10.26719/2019.25.10.715
|View full text |Cite
|
Sign up to set email alerts
|

Cost–benefit analysis of a projected national human papilloma virus vaccination programme in Lebanon

Abstract: Background: The adoption of a population-based human papilloma virus (HPV) vaccination programme is debated in Lebanon on epidemiological, sociocultural, logistical and economic grounds. Aims: This cost-benefit analysis contributes to generating quantitative evidence necessary for a decision regarding costs through locally available data. Methods: The 2 sides of the cost-benefit analysis equation are: estimation of the cost of HPV vaccination campaigns targeting 11 year-old girls, using the cheapest vaccine in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
(18 reference statements)
0
5
0
Order By: Relevance
“… 45 A cost-benefit analysis using the limited available data in Lebanon indicated that massive HPV vaccination targeting 11-year-old girls and using the cheapest vaccine would not be cost-beneficial under the circumstances that were existing in 2016. 46 However, in view of the increasing risky sexual behaviors among the Lebanese population in the past decade 47 - 49 , a periodic re-assessment of the cost-benefit analysis of a national HPV immunization program is recommended. Globally, there are huge disparities in women HPV immunization, with high prevalence in high-income and upper-middle-income countries and low prevalence in low-income and middle-income countries that have the highest CUca incidence and mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 45 A cost-benefit analysis using the limited available data in Lebanon indicated that massive HPV vaccination targeting 11-year-old girls and using the cheapest vaccine would not be cost-beneficial under the circumstances that were existing in 2016. 46 However, in view of the increasing risky sexual behaviors among the Lebanese population in the past decade 47 - 49 , a periodic re-assessment of the cost-benefit analysis of a national HPV immunization program is recommended. Globally, there are huge disparities in women HPV immunization, with high prevalence in high-income and upper-middle-income countries and low prevalence in low-income and middle-income countries that have the highest CUca incidence and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…45 A cost-benefit analysis using the limited available data in Lebanon indicated that massive HPV vaccination targeting 11-year-old girls and using the cheapest vaccine would not be cost-beneficial under the circumstances that were existing in 2016. 46 However, in view of the increasing risky sexual behaviors among the Lebanese population in the past decade [47][48][49] , a periodic re-assessment of the cost-benefit analysis of a national HPV immunization program is recommended. Globally, there are huge disparities in women 17 5.8 Israeli non-Jews (2012) 22 5.3 Israeli Jews (2012) 22 5.2 Jordan (2012) 24 1.3 Kuwait-Kuwaiti (2012) 22 3.2 Bahrain (2008-2012) 23 4.1 Saudi Arabia-Saudi (2013) 25 1.5 Iran, Golestan (2008-2011) 23…”
Section: Discussionmentioning
confidence: 99%
“…In addition to breast cancer, colon cancer, and HBV, lung cancer screening is advocated in Lebanon using an annual low-dose CT scan of the chest but remains with very limited applicability. Women are encouraged to do cervical cancer by PAP smear screening through a national campaign for the prevention of cervical cancer [19].…”
Section: Cancer Screening Programsmentioning
confidence: 99%
“…The HPV prevention vaccine is supported for the prevention of cervical cancer. However, a populationbased vaccination program for cervical cancer is still not established [19].…”
Section: Cancer Prevention Programsmentioning
confidence: 99%
“…Even in many LMICs, cervical cancer is the most common cause of cancer deaths, with half a million new cases diagnosed worldwide each year, with nearly 250 000 deaths ( 4 ). Relatively effective methods are available today in the management of this cancer ( 5 ).…”
Section: Introductionmentioning
confidence: 99%